GEOTECHNICAL ENGINEERING DESIGN FOR SETTLEMENT MITIGATION IN THE DEEP FOUNDATION CONSTRUCTION AREA, NORTH SUMATRA PROVINCE, INDONESIA - Malik Muhammad, Kemal; Sophian, Raden Irvan; Helmi, Faisal; Prasetyo, Rahmat Dwi; Damanhuri, Hilman (Bulletin of Scientific Contribution, 2024)
The construction project in area Y, North Sumatra will be installed with piles as the preliminary foundation for a multi-story building. The installation of these piles resulted in settlement at several boreholes points analyzed using Rocscience Settle3. The settlement ranged from 65 mm - 95 mm at over 11 boreholes over the construction area. This settlement has the potential to cause structural damage to the building, therefore geotechnical engineering is needed as a solution to prevent it. Ground improvement as geotechnical engineering can be done to support the design of safer foundations by increasing soil consistency in shallow to deep layers. Vibro compaction geotechnical engineering reduces the total settlement of the research area from 90 mm to 68 mm in BH-01, BH-04, and BH-06. In boreholes with low bearing capacity and medium settlement values such as BH-1, monitoring using a settlement gauge is required to provide efficient prevention in safe foundation planning without neglecting cost effective concern.